Hubungan Penggunaan Media Sosial (Instagram) dengan Etika Moralitas Remaja di SMP Negeri Banjarmasin - Muhsinin, Muhsinin; Alfia, Luthfi (Journal of Nursing Invention, 2024)
The internet and social media like Instagram are often used contrary to ethical and moral values. Behaviors contrary to ethical and moral values are predominantly carried out by adolescents. Behaviors against ethical and moral values that are commonly practiced such as accessing pornographic sites and exploitation of sexuality. Teenagers with all their characteristics often lead to behaviors that are responded to by the community and should not be done by teenagers. This study aims to determine the relationship between the use of social media (Instagram) with the morality of teenagers in SMP Negeri Y Banjarmasin. The research method uses quantitative analytic with cross sectional approach. The number of research samples is 71 respondents. The sample using Proportional Simple Random Sampling technique. Place of research at SMP Negeri Y Banjarmasin. The data analysis technique uses the Spearman Rank and the research instrument is a questionnaire. The results of this study indicate that there is a positive and significant relationship between the use of social media (Instagram) with the ethics of adolescent morality, (p = 0,000 <0.05) with a correlation coefficient of 0.586 moderate relationship strength. Suggestions in this study can be used as a reference in enriching knowledge about the use of social media (Instagram) on the morality ethics of teenagers and can be used properly.